Complexity of Nigerian Company Income Tax Act (CITA 2007): Readability assessment - Umar, Musa Sulaiman (2013)
Simplification of tax laws in terms of readability to aid easier and complete compliance by taxpayers is a key issue to achieving the objectives of every country’s tax system. The connection between language and compliance is obvious and understanding of the laws is crucial for all stakeholders to be able to carry out their respective responsibilities (Tan & Tower, 1992). In particular, simple tax laws would reduce the burden of compliance costs. Under the self-assessment system (SAS) regime, the simplicity of the tax laws is very important as most responsibilities defined by the laws have been shifted to the taxpayers. Thus, complexity of the tax laws may be an obstacle to both the taxpayer and the SAS. This study examines the readability of the Nigerian Company Income Tax Act 2007 (CITA 2007) and explores its association with compliance and administrative costs and SAS of taxation. The study employs readability formulae (Flesch Reading Ease Score and Flesch-Kincaid Grade Level), Average Sentence Length (ASL) and Percentage of Passive Voice (PPV) to determine the level of readability of the Act. Furthermore, this study adopts interview approach to triangulate the readability results obtained using the above formulae, and explores the association between the readability of the Act and compliance costs, administrative costs and SAS. The study found that the CITA 2007 has low level of readability which made the Act very difficult to understand. The low level of readability is also found to be associated with increased compliance costs as well as administrative costs, which subsequently impair the progress of the SAS in Nigeria. The study recommends that tax simplification policy in Nigeria should include language simplification in order to reduce compliance costs and administrative costs. With this tax simplification effort, it is hoped that tax compliance under the SAS can be improved and more tax revenue can be generated